Mi van a megtérésen túl? I. rész: A lelki formálódás teológiai alapjai - SZABÓNÉ LÁSZLÓ , Lilla (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
What is beyond conversion? Part I. The theological foundations of spiritual formation Both the soullessness of our times, the spiritual overheating, and the unfolding pragmatism in the field of spiritual life call for practical theology to reflect on the field of spiritual formation. In our Church, in our congregations, evangelization, the call to conversion, is still at the heart of the matter. Little is said about what is or what should be after conversion? In this paper, we will reflect theologically on the subject of spiritual formation. We will examine the ordo salutis discussed in classical dogmatics, and within it the interpretations of justification, conversion, and regeneration. Finally, we will explore the theme of sanctification, what is the responsibility of man in the process of spiritual formation according to the Reformed theological approach.